The Suffrage of Foreigners in the Municipal Elections from 2011 to 2019 in Spain - David Moya Malapeira; Alba Viñas (Migraciones, 2021)
The current study takes stock of the accumulated experience in political participation at municipal elections of non-EU citizens in 2011, 2015 and 2019. It does so by framing the data and outcomes within the existing regulatory framework in Spain, a framework that very strongly conditions such participation. The text reviews the implications of the model of selective recognition of the right to vote (based on the voter’s nationality), and analyzes certain legal conditions steaming from the requirements of reciprocity, residence or previous census registration. The authors consider that the cumulative impact of those conditions is responsible for the very low electoral turnout in non-EU citizens participation. Lastly, the authors present some ideas to overcome such effect and make the most of the present model, at least until its replacement in municipal elections by a truly universal suffrage model.